Orthorexia nervosa and social media: A mixed-methods scoping review using a systematic methodology - Emmanuelle Awad; Jessica M. Alleva; Celine El Khoury; Nour Chamma; Carolien Martijn; Rana Rizk (PLoS ONE, 2026)
Introduction Orthorexia Nervosa (ON) is defined as a preoccupation with abiding by a self-perceived healthy diet resulting in pathological thought, behavior and emotion. Social media platforms may add to this preoccupation with healthy eating by offering accessible exposure to food and dieting information. Yet, the precise nature of the association between ON and exposure to social media remains underexplored. The aim is to explore the existing literature on the relationship between social media and ON in a scoping search and to synthesize the findings. Methods We searched PubMed, Web of Science, PsycInfo (Ovid), ProQuest, and Embase (Elsevier). As for the grey literature, we searched ProQuest Dissertations and Open Access Theses and Dissertations. The first literature search was conducted on August 7, 2023 then a literature update on September 18, 2024. Results After the identification of studies and data extraction, authors assessed the methodological quality of included studies. The characteristics and findings from the studies were narratively synthesized, with a focus on the platform, duration, and content of social media use. A total of 31 studies were identified between 2017 and 2024, which were predominantly cross-sectional and focused on Westernized populations. The results have shown a bidirectional relationship between ON and social media, influenced by the characteristics of the platform (e.g., image-based), duration of use (e.g., longer use), content themes (e.g., diet and fitness-related), and individual-level factors (e.g., limited health literacy, young adulthood and adolescence, and body dissatisfaction). Conclusion The main research gaps found were the absence of experimental studies, lack of studies in non-Westernized populations, restrictive samples, and lack of investigations about developmental pathways. Longitudinal, experimental and qualitative studies in future research are warranted to advance knowledge. Systematic review registration: Open Science Framework (OSF) Registries (DOI https://osf.io/vrqwt ).